Hemophilus Para-Influenzae Meningitis in a Two-Day-Old Term Infant - Rahbar, Fariborz (1985)
A two-day-old black male term infant developed meningitis due to Hemophilus para-influenzae, a rare cause of neonatal meningitis. The organism was sensitive to ampicillin and chloramphenicol. Of interest was that the mother had the same organism in her cervix. The need for prompt investigation and institution of appropriate antibiotic therapy is emphasized.